Twelve Month outcome analysis of a South African Intensive Care Unit. - Erwee, Daniel (Department of Medicine, 2024)
Abstract Background: The description of outcomes after admission to Critical Care Units in Africa is sparse, reporting mortality rates between 23.6% and 53.6%. South African data, thus far, show in-ICU mortality rates between 9% and 19.7%. To our knowledge, no evaluation of ICU outcomes has ever been performed on a population group in the Western Cape Province. Objectives: To describe patients admitted to an 8-bed ICU unit over one calendar year with regards to demographics and outcomes situated in Groote Schuur Hospital with regard to inICU and 1-year mortality rates. Methods: This is a retrospective descriptive review of adult patients (>18 years old) from 1 January 2019 to 31 December 2019. Data were collected on age, sex, primary admission diagnosis, length of stay and mortality. Results: A total of 338 patients were included; 61.2% (n=207) with a primary medical diagnosis and 38.2% (n=129) with a non-medical diagnosis. Trauma accounted for 13.6% of all admissions. The burden of known HIV infection as a comorbidity was 16.9% (n=57). The overall in-ICU mortality rate was 25.7% (n=87), and the one-year mortality rate was 18.0% (n=25), but with a significant loss to follow-up of 33.1%. Conclusion: The overall in-ICU mortality was 25.7%. A large proportion of patients admitted had a trauma diagnosis, despite it historically accepting mostly medical and complicated obstetric patients.